(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents the results of the study of enrichment of antimony from manmade wastes by flotation method. Filtration scheme on disk vacuum filter is considered. A special gravity separator was made with a height of 12 cm, a diameter of 10 cm. It was established that in the process of gravity antimony waste is classified into light and heavy fractions, the separation of fractions depends on the molecular weight of the substances. An increase in the recovery of oxidized antimony was carried out based on the selection of the reagent regime. X-ray fluorescence method investigated chemical composition of man-made wastes (dump cake) of KSK. A 16.5% solution of a magnesia mixture (MgCl2 + NH4Cl + NH4OH) in excess of ammonium hydroxide was used to recover and precipitate arsenic and iron ions.